1996
DOI: 10.1590/s0036-46651996000200009
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni: the sex ratios of worms in animals infected with cercariae from three species of Biomphalaria

Abstract: The ratios of male to female worms of Schistosoma mansoni were determined in mice infected with cercariae from LE, SJ and AL strains shed by mollusc hosts of the parasite in Brazil. The sex ratios of worms in the animals were similar with cercariae from Biomphialaria glabrata and B. tenagophila varying from 1.1:1 to 1.6:1 with LE and AL strains and 1:1.1 with SJ. In the animals infected with cercariae from B. straminea the ratio of male to female worms was similar to those obtained using cercariae shed from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…It has been demonstrated that the sex ratio of S. mansoni is male biased, displaying male:female ratios of 1.1:1 to even 6:1 in infected mice, depending on the strain of the intermediate host. 35 Furthermore, male adults have a greater biomass than females, which attributes to the male bias even more. However, the effect of this overrepresentation of proteins derived from male worms has to be considered minor, since a recent study comparing the proteomes of male and female S. japonicum parasites shows that adult female worms express relatively low number (2.46%) of female-specific proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the sex ratio of S. mansoni is male biased, displaying male:female ratios of 1.1:1 to even 6:1 in infected mice, depending on the strain of the intermediate host. 35 Furthermore, male adults have a greater biomass than females, which attributes to the male bias even more. However, the effect of this overrepresentation of proteins derived from male worms has to be considered minor, since a recent study comparing the proteomes of male and female S. japonicum parasites shows that adult female worms express relatively low number (2.46%) of female-specific proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It has to be noted that proteins from male adult worms are probably overrepresented in our samples. It has been demonstrated that the sex ratio of S. mansoni is male biased, displaying male:female ratios of 1.1:1 to even 6:1 in infected mice, depending on the strain of the intermediate host …”
Section: Discussionmentioning
confidence: 99%
“…The normal adult worm sex-ratio in Brazil is male biased (Souza et al 1996). The origin of this bias is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of this tag strongly suggests that this is the most abundant mRNA species found in adult worms. This abundance is highly significant, especially if we consider the larger biomass of male worms as well as the male bias found in the sex ratio of S. mansoni infections [32]. Indeed, among the top 5% most abundant transcripts of adult worms, we can find other eggshell-related genes such as P40 (146 th most abundant transcript, with 56 tags), P19 (202 nd with 42 tags) and P48 (356 th with 26 tags), which advocates their importance in the early-stages of eggshell formation.…”
Section: Discussionmentioning
confidence: 99%